Efficacy of an Er:YAG laser in the decontamination of dental implant surfaces: An in vitro study - AlMoharib, Hani S; Steffensen, Bjorn; Zoukhri, Driss; Finkelman, Matthew; Gyurko, Robert (Journal of periodontology (1970), 2021)
Emergence of peri-implant diseases led to the development of various methods for implant surface decontamination. This study was designed to compare the efficacy of biofilm removal from implant-like titanium surfaces by an erbium-doped yttrium-aluminum-garnet (Er:YAG) laser, titanium brush, and carbon fiber curet. Eight study subjects were recruited. A custom mouth appliance that held eight sandblasted and acid-etched titanium discs was fabricated for each subject. Subjects were asked to wear this appliance for 72 hours to allow for biofilm development. After retrieval, discs were removed and randomized to one of four treatment groups. The discs were stained with a two-component nucleic acid dye kit, and the residual biofilm was visualized under fluorescence microscopy. Quantification of residual biofilm was performed using an image analysis software and expressed as the percentage surface area. Fifty-nine titanium discs were randomized to the four treatment groups. The percentage of titanium disc area covered by residual biofilm was 74.0% ± 21.6%, 32.8% ± 24.0%, 11.8% ± 10.3%, and 20.1% ± 19.2% in the control, Er:YAG, titanium brush and carbon fiber curet groups, respectively (mean ± SD). The biofilm-covered area significantly decreased in each of the three treatment groups compared with control (P < 0.008). Comparisons between treatment groups did not reveal statistical significance. Er:YAG laser treatment is an effective method for reducing the bacterial biofilm on titanium discs. However, on a threadless titanium surface, Er:YAG laser does not exhibit a significantly greater efficacy in biofilm removal than commonly used titanium brushes or carbon fiber curets.